Maximum ecological function performance for a three-reservoir endoreversible chemical pump - Chen, Lingen; Shi, Shuangshuang; Feng, Huijun; Ge, Yanlin (Journal of non-equilibrium thermodynamics, 2023)
Endoreversible chemical pump (ECP) is a theoretical model of electrochemical, photochemical, solid-state apparatus and mass exchangers. ECP can be classified as two-, three- and four-mass-reservoir devices. The usual performance indicators for ECPs are energy pumping rate (EPR) and coefficient of performance (COP). Energy-based ecological function objective (EFO) is introduced to performance optimization of three-reservoir ECP. Optimization relationships between EFO and COP with linear and diffusive mass transfer laws (MTLs) are deduced. Numerical examples are provided, and influences of cycle parameters and MTLs on optimal EFO performances are analyzed. For linear MTL, compared performances at maximum EFO point and point where dimensionless EPR is 0.016, COP increases 14.4% and entropy generation rate (EGR) drops 52% with only 30% loss of EPR. For diffusive MTL, compared performances at maximum dimensionless EFO point and point where dimensionless EPR is 0.01, COP increases 11.3% and EGR drops 46.9% with only 30% loss of EPR. It demonstrates that EFO is a trade-off between EPR and dissipation of EPR, which is beneficial to utilize energy effectively. With the same chemical potentials of three reservoirs, the maximum dimensionless EFO and the corresponding COP with linear MTL are bigger than those with diffusive MTL.